Seven new species of Limnophora Robineau-Desvoidy (Diptera: Muscidae) from Ecuador - Fogaça,João Manuel (2015)
ABSTRACTHere we describe seven new species of Limnophora from Ecuador: Limnophora bifasciatasp. nov. from Napo, Quito; Limnophora equatoriensissp. nov. from Zamora-Chinchipe, Zamora; Limnophora femurosetalissp. nov. from Zamora-Chinchipe, Zamora; Limnophora lamasisp. nov. from Zamora-Chinchipe, Zamora; Limnophora longivittatasp. nov. from Napo, Quito; Limnophora penaisp. nov. from Azuay, Cuenca and Limnophora polletisp. nov. from Napo, Quito. We provide an identification key for the ten recognized species of Limnophora from Ecuador, including L. marginata Stein, 1904, L. pica(Macquart, 1851) and L. saeva (Wiedemann, 1830). We also redescribed Limnophora marginata Stein, 1904, and designated designed lectotype male and paralectotypes males and females of the species.